Interprofessional education and transitions of care: a case-based educational pilot experience. Issue 3 (4th May 2021) - Bland, Marghuretta; Stevens, Alison; Nellis, Patricia; Mueggenburg, Kay; Yau, Timothy; ChenJustin, C.
ABSTRACT: Interprofessional education is becoming a requirement for accreditation of most health profession programs, therefore it is necessary to share innovative experiences so all can learn from the successes and barriers of implementation. Faculty members from five health profession programs (medicine, nursing, occupational therapy, pharmacy, and physical therapy) were tasked with developing a pilot interprofessional education experience focused on transitions of care. The result was a three-phase experience in which students individually completed online virtual cases, then came together for small- and large-group discussions, and concluded by working through a simulated patient discharge. Objectives centered on recognizing the individual's professional role during transitions of care, identifying barriers to transitions of care, and evaluating strategies to improve safety during a transition. Outcomes were measured using an anonymous pre and post-experience survey. Twenty-three students completed the experience and identified key themes related to their profession's role in, and barriers to a transition of care. The majority of students strongly agreed that this experience has made them more aware of the importance of interprofessional communication, and that they would recommend this pilot experience to a colleague.